A new method to improve the electrical properties of KNN-based ceramics: Tailoring phase fraction. Issue 1 (January 2018) - Lv, Xiang; Wu, Jiagang; Zhu, Jianguo; Xiao, Dingquan; Zhangb, Xixiang
Abstract: Although both the phase type and fraction of multi-phase coexistence can affect the electrical properties of (K, Na)NbO3 (KNN)-based ceramics, effects of phase fraction on their electrical properties were few concerned. In this work, through changing the calcination temperature of CaZrO3 powders, we successfully developed the 0.96 K0.5 Na0.5 Nb0.96 Sb0.04 O3 -0.01CaZrO3 -0.03Bi0.5 Na0.5 HfO3 ceramics containing a wide rhombohedral-tetragonal (R-T) phase coexistence with the variations of T (or R) phase fractions. It was found that higher T phase fraction can warrant a larger piezoelectric constant ( d 33 ) and d 33 also showed a linear variation with respect to tetragonality ratio ( c / a ). More importantly, a number of domain patterns were observed due to high T phase fraction and large c / a ratio, greatly benefiting the piezoelectricity. In addition, the improved ferroelectric fatigue behavior and thermal stability were also shown in the ceramics containing high T phase fraction. Therefore, this work can bring a new viewpoint into the physical mechanism of KNN-based ceramics behind R-T phase coexistence.